Tinjauan Pelaksanaan Perhitungan, Penyetoran Dan Pelaporan Pajak Penghasilan Pasal 25 Pada PT Makassar Hotel Network - Dian Kurniasari; Nurul Afifah; ilh Ilham (Income Journal: Accounting, Management and Economic Research, 2022)
PT Makassar Hotel Network is a subsidiary of PT Bosowa Propertindo which is operating in hospitality services. PT Makassar Hotel Network has an obligation to pay income tax. If the tax payment is done at once, it will certainly be burdensome, therefore PT Makassar Hotel Network pays taxes in installments every month or is called Income Tax Article 25. This study aims to determine the calculating, tax payment and tax report Income Tax Article 25 on PT Makassar Hotel Network. Data analysis technique in this research is qualitative descriptive analysis. Data to be processed is data on the amount of Income Tax Article 25 calculating, tax payment data and tax report data. The results of the study is indicate that the calculating and tarrif (25%) used was in accordance with the applicable tax regulations. In addition, tax payment and tax report are in compliance with the prevailing taxation regulations which are deposited prior to the 15th of the following month after the expiration of the tax period and the reporting is made before the 20th of the following month after the expiration of the tax period.